2019
DOI: 10.1111/cen3.12528
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment as one of the important non‐motor symptoms in multiple sclerosis and neuromyelitis optica spectrum disorders

Abstract: Cognitive impairment is one of the most important non-physical symptoms of patients with multiple sclerosis (MS), and few studies have reported on cognitive impairments in patients with neuromyelitis optica spectrum disorders. Adequate batteries are required to assess cognitive function in MS, and cognitive impairments in patients with MS are likely not adequately evaluated. As cognitive impairment usually affects employment status and activities of daily living in patients with MS and neuromyelitis optica spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…On the other hand, some cross-sectional studies have found only a weak correlation 45 or no correlation between disease duration and CI. 46 47 In our study, the disease duration had a significant positive correlation with CI severity, and the mean disease duration was significantly longer in the CI group than in the NCI group.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, some cross-sectional studies have found only a weak correlation 45 or no correlation between disease duration and CI. 46 47 In our study, the disease duration had a significant positive correlation with CI severity, and the mean disease duration was significantly longer in the CI group than in the NCI group.…”
Section: Discussionsupporting
confidence: 49%
“…Despite its previous identification by Charcot ( 78 ), it has been overlooked for a long time. Our data over the past two decades showed that neuropsychological symptoms have been increasingly investigated, of which cognition, depression, and fatigue were among the most important ( 79 ). Furthermore, rehabilitation appeared among the top keywords in the analyzed data, which had been a neglected area of MS research as well ( 56 ).…”
Section: Discussionmentioning
confidence: 98%
“…Because brain reserve is potentially modifiable, 11 early detection and intervention of triggers that disconnect brain networks are crucial for preserving brain reserve and preventing cognitive decline. Additionally, as patients may be unaware of cognitive decline in CIDDs, a sensitive and easily accessible screening tool is essential for monitoring cognitive function 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Because brain reserve is potentially modifiable, 11 early detection and intervention of triggers that disconnect brain networks are crucial for preserving brain reserve and preventing cognitive decline. Additionally, as patients may be unaware of cognitive decline in CIDDs, a sensitive and easily accessible screening tool is essential for monitoring cognitive function 12 .The Symbol Digit Modalities Test (SDMT) is the predominant and widely accepted cognitive assessment tool for CIDDs [13][14][15] . This evaluation involves associating numbers with corresponding symbols within a 90 s timeframe, referencing a table with nine-digit-symbol pairs 16 .…”
mentioning
confidence: 99%